Philosophical Foundations for Developing an Anti-Corruption Based Islamic Religious Education Curriculum - Munawar, Fuad; Nugraha, Mulyawan Safwandy (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
This research is motivated by the widespread practice of corruption, collusion, and nepotism, especially in the education sector. The purpose of this article is to describe the overall philosophical aspects underlying the development of the Islamic Religious Education curriculum which focuses on preventing corruption based on KMA 183 and 184 of 2019. This research is qualitative with a literature review approach. Data sources come from documentation in the form of books and scientific articles that review the philosophical aspects of anti-corruption-based PAI curriculum development. Data is collected through documentation techniques, which involve selecting relevant data for the research topic. Next, an investigation was carried out using various sources such as books, journals, articles, papers, and other reference materials relevant to this research. Anti-corruption education values should not only be seen as a hidden curriculum but must have reached the stage of integration with the material in PAI subjects, up to the stage of preparing specific material related to the implementation of anti-corruption education values that are in line with the mandate of the revelation. If the anti-corruption-based PAI curriculum is only seen as a hidden curriculum, concerns about its implementation will become blurred and unfocused.